2017
DOI: 10.1016/j.ebiom.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Uncovers a Growth-Promoting Activity of Orosomucoid-1 on Hepatocytes

Abstract: The acute phase protein orosomucoid-1 (Orm1) is mainly expressed by hepatocytes (HPCs) under stress conditions. However, its specific function is not fully understood. Here, we report a role of Orm1 as an executer of HPC proliferation. Increases in serum levels of Orm1 were observed in patients after surgical resection for liver cancer and in mice undergone partial hepatectomy (PH). Transcriptome study showed that Orm1 became the most abundant in HPCs isolated from regenerating mouse liver tissues after PH. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
(66 reference statements)
0
28
0
Order By: Relevance
“…Formalin-fixed, paraffin-embedded liver tumor tissues and normal adjacent tissues of HCC patients were obtained from Gifu University or were purchased from ProteoGenex ( 20 ). cDNA samples were synthesized from liver biopsies that were obtained from 12 HCV-positive patients whose HCC had been eradicated through curative resection or ablation and who underwent a liver biopsy at baseline and during week 8 of treatment with a daily dose of either 300 or 600 mg ACR at Kanazawa University Hospital (Kanazawa, Japan) ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formalin-fixed, paraffin-embedded liver tumor tissues and normal adjacent tissues of HCC patients were obtained from Gifu University or were purchased from ProteoGenex ( 20 ). cDNA samples were synthesized from liver biopsies that were obtained from 12 HCV-positive patients whose HCC had been eradicated through curative resection or ablation and who underwent a liver biopsy at baseline and during week 8 of treatment with a daily dose of either 300 or 600 mg ACR at Kanazawa University Hospital (Kanazawa, Japan) ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Members of the MYC family of basic helix–loop–helix–zipper transcription factors, including MYC (c-Myc), MYCL (L-Myc), and MYCN (N-Myc), are central regulators of growth-promoting signal transduction that maintain stem cell pluripotency ( 18 ). The MYC family members play dual roles in regulating normal stem cell-mediated tissue regeneration and CSC-mediated tumorigenesis, which share common molecular pathways in controlling cell growth ( 19 , 20 ). During repeated liver damage and compensatory regenerations, aberrant stabilization and activation of c-Myc have contributed to the development of liver cancers ( 21 ).…”
mentioning
confidence: 99%
“…Genes correlated with SCD1 gene expression in colon cancer were selected through an analysis of the TCGA database using cBioPortal software [39]. With a threshold of Spearman's correlation coefficient of >0.2, 806 genes were selected and input into the knowledge-based functional analysis software IPA (Ingenuity Systems) as previously described [40]. The generated biological networks were ranked by score, which is the likelihood of a set of genes being found in the networks owing to random chance, identified by a Fisher's exact test.…”
Section: Knowledge-based Pathway Analysismentioning
confidence: 99%
“…For the metabolome analysis, the pathway impact was calculated as the sum of the importance measures of the matched metabolites normalized by the sum of the importance measures of all metabolites in each pathway using MetaboAnalyst 4.0 50 . For the transcriptome analysis, the knowledge-based functional analysis was performed using the IPA platform (Ingenuity Systems, Mountain View, CA, USA) as previously described 19 . The generated biological networks were ranked by score, which is the likelihood of a set of genes being found in the network owing to random chance, identified by a Fisher's exact test.…”
Section: Knowledge-based Pathway Analysismentioning
confidence: 99%
“…v-myc avian myelocytomatosis viral oncogene neuroblastoma derived homolog (MYCN), is a well-recognized oncogene associated with the progression and prognosis of neuroblastoma 18 . A transcriptome analysis performed by our group in primary hepatocytes during the process of mouse liver regeneration revealed that the expression of Mycn was low in normal hepatocytes, but increased along with hepatocyte proliferation after partial hepatectomy 19 . We also reported that MYCN expression was seen in epithelial cell adhesion molecule (EpCAM) + liver CSC-like cells and was positively correlated with the recurrence of HCC 20 .…”
Section: Introductionmentioning
confidence: 99%